The discovery of Rock Geckos Cnemaspis Strauch, 1887 (Squamata: Gekkonidae) in the Tanintharyi Region, Myanmar with the description of two new species - Lee, Justin L.; Miller, Aryeh H.; Zug, George R.; Mulcahy, Daniel G. (Zootaxa, 2019)
We report the first occurrence of the Asian Rock Gecko genus Cnemaspis Strauch, 1887 from mainland Myanmar based on a series of specimens recently collected from the Tanintharyi Region. These records come from several localities in the Tanintharyi Region and fill a significant sampling gap for the genus. Molecular phylogenetic analyses using the mitochondrial gene ND2 identify two distinct clades, the first includes Cnemaspis siamensis of the Southeast Asian Cnemaspis group and the second includes two new species belonging to the South Asian Cnemaspis kandiana group. These two species are morphologically distinct and are distinguished from all other members in the C. kandiana group by a combination of character states. The first species, Cnemaspis tanintharyi sp. nov. occurs on the mainland in southern Tanintharyi and is distinguished from all congeners by the possession of keeled pectoral scales; smooth ventral scales and abdominal scales; 2–4 precloacal pores; 4–5 femoral pores on each leg; smooth subcaudal scales with the median row enlarged; coloration of the gular region beige, dark gray-brown with dark blue hueing towards throat; 15–18 subdigital lamellae on the 4th toe; and 21–23 ventral scales at midbody. The other, Cnemaspis thayawthadangyi sp. nov. is known only from the island group of Thayawthadangyi, in the Myeik Archipelago and is distinguished from all congeners by the possession of keeled pectoral scales; keeled ventral scales and abdominal scales; three precloacal pores; four femoral pores on each leg; smooth subcaudal scales, scales on median row enlarged; coloration of the gular region silver with dark-gray irregularly shaped streaks; 16–18 subdigital lamellae on the 4th toe; and 18–20 ventral scales at midbody. In addition, we address the taxonomic status of populations referred to as C. kandiana (a species now restricted to Sri Lanka) found in peninsular Thailand and provisionally assign them as C. cf. tanintharyi sp. nov. until further analysis can be conducted. Finally, we briefly discuss the biogeography of the South Asian clade of Cnemaspis.